A SAW shaping filter for high data rate MSK-encoding in a broadband DS-CDMA system - Zenzinger, Alesander; Morhart, Franz; Reindl, Leonhard; Weigel, Robert (IEEE MTT-S Symposium on Technologies for Wireless Applications Digest, 1997)
We report on two surface acoustic wave (SAW) shaping filters which generate a minimum shift keying (MSK) modulated signal by converting a BPSK modulated signal. The filters are intended to be used for modulators with high data rates, as it is necessary in broadband direct sequence code division multiple access (DS-CDMA) systems. One filter has been fabricated from a lithium tantalate (LiTaO3) substrate, and one from a quartz substrate. The filter on LiTaO3 fulfills all requirements dealing with spectrum shaping. However, the temperature range is not as wide as with quartz substrates due to the higher temperature coefficient of LiTaO3. The filter on quartz is very stable from the temperature coefficient point of view, but the insertion attenuation and spurious electromagnetic feedthrough are relatively high.
elib2cris::1512001600,zenzinger1997a
Keywords: Acoustic waves; Binary phase shift keying; Direct-sequence code-division multiple access; Filters; Lithium compounds; Modulation coding; Multiaccess communication; Signal generators; Surface acoustic waves; Temperature distribution